Factors Responsible for Studentsâ€™ Unrest in Nigerian Tertiary Institutions: Implications for Counselling Practices - Odebode, Aminat Adeola (MIMBAR PENDIDIKAN, 2019)
ABSTRACT: This study, thus, investigated the factors responsible for studentsâ€™ unrest in Nigerian Tertiary Institutions. Further investigation was also done based on moderating variables of age, gender, and religion if they would have any bearing on the participantsâ€™ views. The study was descriptive in nature. The sample consisted of one thousand and two hundred undergraduates, who were selected in six Universities in Nigeria using purposive, simple random, and systematic random techniques. A new questionnaire labelled FRSUQ (Factors Responsible for Studentsâ€™ Unrest Questionnaire) was developed and used to collect data. The results showed that the factors responsible for studentsâ€™ unrest in Nigerian Tertiary Institutions are unfavorable Government policies; poor staff-studentsâ€™ relationship; poor teaching-learning facilities; high tuition fees; and non-responsiveness of University authorities among others. Results also showed that there were no significant differences in the factors responsible for studentsâ€™ unrest in Nigerian Universities based on age, gender, and religion. KEY WORD: Factors Responsible for; Studentsâ€™ Unrest; Nigerian Tertiary Institutions; Counsellors.Â ABSTRAKSI: â€œFaktor-faktor yang Bertanggung Jawab atas Keresahan Mahasiswa di Lembaga Pendidikan Tinggi Nigeria: Implikasi bagi Praktek Konselingâ€. Penelitian ini, dengan demikian, menyelidiki faktor-faktor yang bertanggung jawab atas keresahan mahasiswa di Lembaga Pendidikan Tinggi Nigeria. Penyelidikan lebih lanjut juga dilakukan berdasarkan variabel moderasi usia, jenis kelamin, dan agama jika mereka memiliki pandangan yang berbeda terhadap peserta. Penelitian ini bersifat deskriptif. Sampel terdiri dari seribu dua ratus mahasiswa, yang dipilih di enam Universitas di Nigeria menggunakan teknik sampel acak bertujuan, sederhana, dan sistematis. Kuesioner baru berlabel FRSUQ (Kuesioner Faktor-faktor yang Bertanggung Jawab atas Keresahan Mahasiswa) dikembangkan dan digunakan untuk mengumpulkan data. Hasil penelitian menunjukkan bahwa faktor-faktor yang bertanggung jawab atas keresahan mahasiswa di Lembaga Pendidikan Tinggi Nigeria adalah kebijakan Pemerintah yang tidak menguntungkan; hubungan staf-mahasiswa yang lemah; fasilitas belajar-mengajar yang buruk; biaya kuliah yang tinggi; serta tidak responsifnya pihak otoritas Universitas antara lain. Hasil kajian juga menunjukkan bahwa tidak ada perbedaan signifikan dalam faktor-faktor yang bertanggung jawab atas keresahan mahasiswa di Universitas Nigeria berdasarkan usia, jenis kelamin, dan agama. KATA KUNCI: Faktor-faktor yang Bertanggung Jawab atas; Keresahan Mahasiswa; Lembaga Pendidikan Tinggi Nigeria; Pembimbing.About the Author: Dr. Aminat Adeola Odebode is a Lecturer at the Department of Counsellor Education UNILORIM (University of Ilorin), Nigeria. For academic interests, the Author is able to be contacted via e-mail adrress at: odebode.aa@unilorin.edu.ng Â Suggested Citation: Odebode, Aminat Adeola. (2019). â€œFactors Responsible for Studentsâ€™ Unrest in Nigerian Tertiary Institutions: Implications for Counselling Practicesâ€ in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Volume 4(2), September, pp.93-102. Bandung, Indonesia: UPI [Indonesia University of Education] Press, ISSN 2527-3868 (print) and 2503-457X (online). Article Timeline: Accepted (July 3, 2019); Revised (August 17, 2019); and Published (September 30, 2019).